The impacts of individualization on equity educational policies - Guadalupe Francia (Springer, 2013)
The present article has as its aim to illustrate and discuss the impacts of individualization strategies on equity educational policies through the analysis of individualized teaching strategies applied within the framework of educational priority policies in Sweden. The methodology used in our research work includes: (a) the study of research literature about the individualization of teaching implemented in the Swedish comprehensive compulsory school; and (b) the study of research literature about educational priority policies aimed at children from socially and ethnically segregated areas. Comparative research of educational policies considers the individualization of teaching carried out in the Swedish comprehensive compulsory school as a relevant explanation for the successful application of equitable educational policies in that country. However, research studies published during the 2000s in Sweden show a more complex perspective regarding the effects of individualized teaching strategies. This contribution reviews European comparative research studies on individualization strategies followed in the context of equity policies. It raises questions about the lack of analyses referring to the impacts of individualization on schools located in socially and ethnically segregated areas. It argues that this ideology tends to reduce the issue of school failure to ethnic segregation and individualized teacher support. This article claims that Individualization strategies based on differentiated curricula for students run the risk of increasing the discrimination of students for reasons of language or ethnic background. Even though the present study focuses on the Swedish experience, it can lead to a better understanding of the impacts caused by individualization strategies on equity in other European countries.